The Effect of Electrospinning Parameters on Morphological and Mechanical Properties of PAN-based Nanofibers Membrane - Haneen S. Al-Okaidy; Basma I. Waisi (مجلة بغداد للعلوم)
The electrospun nanofibers membranes (ENMs) have gained great attention due to their superior performance. However, the low mechanical strength of ENMs, such as the rigidity and low strength, limits their applications in many aspects which need adequate strength, such as water filtration. This work investigates the impact of electrospinning parameters on the properties of ENMs fabricated from polyacrylonitrile (PAN) solved in N, N-Dimethylformamide (DMF). The studied electrospinning parameters were polymer concentration, solution flow rate, collector rotating speed, and the distance between the needle and collector. The fabricated ENMs were characterized using scanning electron microscopy (SEM) to understand the surface morphology and estimate the average fiber sizes. The membrane porosity percentage was measured using the dry-wet weight method. Also, a dynamic mechanical analyzer was used to determine the mechanical strength properties (tensile strength and Young's modulus) (DMA). The obtained results revealed that the polymer concentration and flow rate mainly affect the porosity and fiber size in ENMs. Increasing the polymer concentration improves the strength and flexibility, while the flow rate did not show a clear effect on the mechanical strength of ENMs. Both fibers collecting speed and spinning distance did not clearly impact the membrane morphology. ENMs flexibility significantly increased with increasing the collector speed and decreasing the spinning distance. Strong and flexible ENMs with small fibers can be fabricated using 10% PAN/DMF at a flow rate of 1 mL/h, collector speed of 140 rpm, and spinning distance of 13 cm.